Migraine - Sacks, Oliver, 1933-2015 (Vintage Books, 1999)
The many manifestations of migraine can vary dramatically from one patient to another, even within the same patient at different times. Among the most compelling and perplexing of these symptoms are the strange visual hallucinations and distortions of space, time, and body image which migraineurs sometimes experience. Portrayals of these uncanny states have found their way into many works of art, from the heavenly visions of Hildegard von Bingen to Alice in Wonderland. Renowned neurologist Dr. Oliver Sacks argues that migraine cannot be understood simply as an illness, but must be viewed as a complex condition with a unique role to play in each individual's life.--From publisher description.